Silo Mentality in Stunting Reduction Programs in Southeast Sulawesi - Abidin, Zainul; Asmiddin, Asmiddin; Parasit, La (Universitas Medan Area, 2025)
This article aims to analyze how silo mentality affects the effectiveness of stunting reduction program implementation in three regencys in Southeast Sulawesi: Buton, Central Buton, and South Buton. The problem is centered around silo mentality and it’s affects. To adress this issue theoretical references are employed. Data is collected through in-depth interviews and analysis of local policy documents. The study concludes that that silo mentality is manifested in the form of non-integrated planning, weak collaborative commitment between OPDs, fragmentation of information systems, and passive leadership towards cross sector work. Despite the existence of convergence planning documents, implementation in the field is still procedural and administrative, without substantive coordination. This finding reinforces public organization theory which states that institutional reform and organizational culture change are key prerequisites for cross sector policy success.